Tinjauan Pustaka Sistematis: Faktor yang Mempengaruhi Hasil Pengobatan pada Pasien Tuberkulosis Multidrug-Resistant - Mega Novitasari; Hidayah Karuniawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Multidrug-Resistant Tuberculosis (MDR-TB) is a disease caused by resistant Mycobacterium tuberculosis and is a leading cause of death worldwide. Several factors influence treatment outcomes in MDR-TB patients. Objective: This study aims to analyze factors that play an important role in the treatment outcome of MDR-TB patients. Methods: The method used in this study was a systematic literature review with quantitative data. The literature used in this study was obtained through online searches using reputable databases, namely Science Direct, PubMed, and Google Scholar with covering articles from 2020 to 2025. Results: A total of 8 articles met the inclusion criteria and were analyzed in this systematic review. Treatment success rates for MDR-TB patients in several countries ranged from 54,1% to 84.74%. Factors associated with treatment outcome included gender, age, education level, distance to treatment center, body mass index (BMI), time to diagnosis more than 30 days, delayed culture conversion time more than 2 months, history of previous TB treatment, comorbidities, extent of lung lesions and bronchiectasis, and drug side effects. Conclusion: The success rate of MDR-TB treatment in across countries still varies. The success of MDR/RR-TB treatment is influenced by a combination of demographic, clinical, social, and healthcare access factors. Factors such as younger age, good nutritional status, higher education level, and adequate access to healthcare services have been shown to increase the likelihood of treatment success. Conversely, treatment failure (outcome failure) is influenced by the presence of comorbidities, older age, previous treatment history, drug resistance, adverse effects of therapy, delayed diagnosis, and low patient adherence. Early identification of risk factors is essential for optimal management and increased success of MDR-TB treatment.